Judiciaries in comparative perspective - Lee, H. P. (Cambridge University Press, 2011)
An independent and impartial judiciary is fundamental to the existence and operation of a liberal democracy. Focusing on Australia, Canada, New Zealand, South Africa, the United Kingdom and the United States, this comparative study explores four major issues affecting the judicial institution. These issues relate to the appointment and discipline of judges; judges and freedom of speech; the performance of non-judicial functions by judges; and judicial bias and recusal, and each is set within the context of the importance of maintaining public confidence in the judiciary. The essays highlight important episodes or controversies affecting members of the judiciary to illustrate relevant principles.